PARADIGMA PERUBAHAN HUKUM ISLAM (Eksplorasi Pemikiran Ibnu Qayyim al-Jauziyah) - Sitti Rahmawati (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2017)
AbstractIbn Qayyim al-Jauziyah was commonly considered as a liberal Muslim thinker. In his thought about legal changes, he proposes five agents of changes, i.e. time, space, situation, intention, and custom. The legal changes, therefore, occur due to the changes of the five factors. Benefits can only by responding to the changes. Kata Kunci: Perubahan, Hukum, Ibnu Qayyim al-Jauziyah